A Case Study Of Lenovo Global Competition - Debing, Li (2005)
Lenovo Group Ltd (formerly known as Legend Group Limited) is an information technology (IT) corporation in the People's Republic of China. The company is engaged in the manufacture and sales of desktop personal computers, notebook computers, mobile handsets, servers and peripherals.